2019
DOI: 10.1007/s40430-019-1586-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of textured carbide tools under environment-friendly minimum quantity lubrication turning strategies

Abstract: Present investigation is focused to study the impact of different lubricating environments using pure canola oil and graphene mixed in canola oil, on the performance of uncoated carbide textured tools in minimum quantity lubrication (MQL) turning of AISI 4340 hardened steel. The influence of using twin jet and single jet was also studied under MQL. The turning performance was evaluated in terms of flank wear (VB max), cutting forces, cutting temperature, and chip morphology. The results showed that MQL mist su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 41 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…10 ns) was used. The diameters(f ) of dimples were 80 mm, 50 mm deep at a distance of 150 mm from the main cutting edge and the center distance between each dimple is 150 mm, as indicated in Figure 1 (Sharma and Pandey, 2017;Singh et al, 2019a). The inserts were then cleaned with a 20-minute ultrasonic bath in acetone solution.…”
Section: Methodsmentioning
confidence: 99%
“…10 ns) was used. The diameters(f ) of dimples were 80 mm, 50 mm deep at a distance of 150 mm from the main cutting edge and the center distance between each dimple is 150 mm, as indicated in Figure 1 (Sharma and Pandey, 2017;Singh et al, 2019a). The inserts were then cleaned with a 20-minute ultrasonic bath in acetone solution.…”
Section: Methodsmentioning
confidence: 99%
“…Usually, tool wear influences directly the quality of the finished part and manufacturing costs; however, wear is an inevitable phenomenon. The influence of various lubricating surroundings by pure canola oil and graphene mixed in canola oil, on the output characteristics of textured carbide uncoated tools in MQL based AISI 4340 turning has been studied effectively [72].…”
Section: Tool Wear Phenomenonmentioning
confidence: 99%
“…Other researchers [20][21][22] also studied the enhancement in machinability in terms of drill life using grooving or texturing on the drill bit. Singh et al [23] investigated the textured carbide tool under the MQL condition. It is revealed that the texturing on the carbide tool reduces chip curl diameter and improves tool life compared to dry cutting.…”
Section: Introductionmentioning
confidence: 99%